Experimental evidence of cavitation influences on the positive slope on the pump performance curve of a low specific speed model pump-turbine. (December 2017) - Lu, Guocheng; Zuo, Zhigang; Sun, Yuekun; Liu, Demin; Tsujimoto, Yoshinobu; Liu, Shuhong
Abstract: The positive slope on the pump performance curve of pump-turbines suggests potential operational instabilities in pump mode. Previous research has indicated that the positive slope instability can be affected by cavitation conditions, however the detailed influences remain poorly understood. A low specific speed model pump-turbine was systematically examined by experiments for the first time in the present study. A new finding was made that the positive slope is alleviated at the large guide vane opening with decreasing cavitation coefficient, while there is little influence by cavitation at the medium opening. The positive slope occurs at larger discharge coefficient at the small opening when the cavitation coefficient decreases. FFT (Fast Fourier Transformation) results of pressure fluctuations revealed the occurrence of rotating stall close to the vaneless space between the runner and the guide vanes. The variation of cavitation coefficient influences greatly on the occurrence of rotating stall, but the pressure fluctuation frequency caused by rotating stall does not vary significantly. It is postulated that the influence of cavitation coefficient on the rotating stall may be responsible for the variation of the positive slope region. Highlights: Positive slope is alleviated at large guide vane opening with decreasing cavitation coefficient. Positive slope occurs at larger discharge coefficient at the small opening when the cavitation coefficient decreases. Variation of cavitation coefficient influences greatly the occurrence of rotating stall.